Pemanfaatan Buku KIA Sebagai Bentuk Kesiapan Ibu Hamil Primigravida Dalam Perawatan Bayi Baru Lahir - Rohani, Asri; Kusmiwiyati, Ari; Wandi, Wandi (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
The KIA handbook is a guideline to broaden the knowledge of pregnant women about newborn care. Baby care that is carried out by the mother correctly and appropriately will ensure a healthy life for the baby. This study aims to determine the relationship between the use of KIA books and the readiness of primigravida pregnant women in caring for newborns at the Kedungkandang Public Health Center, Malang City. The correlative analytic study design used a cross-sectional approach, with the population of all TM III primigravida pregnant women who made repeat visits in June-July 2020, taken by total sampling. The research instrument used a questionnaire. The data analysis technique used the Spearman's Rho Test. The results showed that a small portion of the primigravida pregnant women (11.1%) used the MCH handbook, the majority 74.1% used the medium category, and a small portion (14.8%) used the low category. while the results of the readiness of primigravida pregnant women in the care of newborns were mostly (51.9%) ready, and almost half (48.1%) in the unprepared category. The results of data analysis showed that there was a significant relationship between the use of MCH handbooks and the readiness of primigravida pregnant women in caring for newborns (p-value 0.006). The higher the mother's use of the MCH handbook, the higher the mother's knowledge and the more prepared the mother is to take care of her newborn. Keywords: Utilization of MCH Handbook, Readiness of Newborn Care